2000
DOI: 10.1159/000014648
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Melanocyte Functions

Abstract: The effect of melatonin on melanocyte functions was studied by incubating whole-skin organ cultures with melatonin, as well as by assessing melatonin positivity in melanocytes versus dendricity and pigmentation, when arrested in the G2 phase. From this study, it was observed that melatonin positivity is inversely related to the length of UV exposure. Increasing melatonin levels are related to decreasing dendricity and pigment donation during photoresponse in the G2 phase. Melanocyte melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Since tubulin forms the cytoskeleton in dendrites as well as the mitotic spindle, melatonin binding to monomers appears to take place during dark incubation to divert monomers from the cytoskeleton to spindle formation. This has also been observed in organ cultures incubated in melatonin [12] where high melatonin positivity is associated with prominent mitosis.…”
Section: Discussionsupporting
confidence: 53%
“…Since tubulin forms the cytoskeleton in dendrites as well as the mitotic spindle, melatonin binding to monomers appears to take place during dark incubation to divert monomers from the cytoskeleton to spindle formation. This has also been observed in organ cultures incubated in melatonin [12] where high melatonin positivity is associated with prominent mitosis.…”
Section: Discussionsupporting
confidence: 53%
“…The melanopsin system of mammals, expressed in a small subset of retinal ganglion cells, regulating and adjusting circadian rhythms, to the environmental light/dark cycle, known as photoentrainment, was in fact isolated from the photosensitive dermal melanophores of frogs Xenopus laevis responding to light (Daniolos et al 1990; Provencio et al 1998, 2000). Extensive studies on the melanocytes by the present author reveal that these fascinating and versatile cells form a photoresponsive network which reads the environmental seasonal variations in the light cycles (Iyengar 1992ab, 1994, 1996a, 1998abc, 2000) in the same manner. The present work was undertaken to study the organization of this system in the human skin.…”
Section: Introductionmentioning
confidence: 76%
“…Earlier studies have identified the presence of biogenic amines in melanocytes. These include catechol amines as well as indole amines [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Since this activity is cyclical with light and dark phases, both SER & MLT are expressed in these layers. In turn, the indoleamines modulate the melanocyte cell cycle in response to UV exposure [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%